Basic Training of Lobby and Negotiation Techniques In Event Implementation For Zillenial Action Learners - Juliani, Dini Tri; Nurul Sadiyyah, Zulfanida; Sofyan, Fauzan Nugraha (Universitas INABA, 2024)
Lobbying and negotiation are one way to reach an agreement that benefits both parties in relationships with customers or business partners. Good negotiating skills can lead to mutual benefits and maintain long-term business relationships. Lobby and negotiation are also necessary in addressing conflict that may arise in a business context. The research method used in this program is descriptive analysis. The results of this community service program implementation can be seen from two indicators, namely the achievement of the outcomes target and the improvement of the participants' skills measured through material exposure and also simulation that output in the form of application of activity. Basic training in lobbying and negotiation techniques played an important role in improving participants' knowledge and ability to approach interpersonal communication and public speaking capabilities.